Importance of conserving large and old trees to continuity of tree‐related microhabitats - Kozák, Daniel; Svitok, Marek; Zemlerová, Veronika; Mikoláš, Martin; Lachat, Thibault; Larrieu, Laurent; Paillet, Yoan; Buechling, Arne; Bače, Radek; Keeton, William S.; Vítková, Lucie; Begovič, Krešimir; et al. (Conservation biology, 2023)
Protecting structural features, such as tree‐related microhabitats (TreMs), is a cost‐effective tool crucial for biodiversity conservation applicable to large forested landscapes. Although the development of TreMs is influenced by tree diameter, species, and vitality, the relationships between tree age and TreM profile remain poorly understood. Using a tree‐ring‐based approach and a large data set of 8038 trees, we modeled the effects of tree age, diameter, and site characteristics on TreM richness and occurrence across some of the most intact primary temperate forests in Europe, including mixed beech and spruce forests. We observed an overall increase in TreM richness on old and large trees in both forest types. The occurrence of specific TreM groups was variably related to tree age and diameter, but some TreM groups (e.g., epiphytes) had a stronger positive relationship with tree species and elevation. Although many TreM groups were positively associated with tree age and diameter, only two TreM groups in spruce stands reacted exclusively to tree age (insect galleries and exposed sapwood) without responding to diameter. Thus, the retention of trees for conservation purposes based on tree diameter appears to be a generally feasible approach with a rather low risk of underrepresentation of TreMs. Because greater tree age and diameter positively affected TreM development, placing a greater emphasis on conserving large trees and allowing them to reach older ages, for example, through the establishment of conservation reserves, would better maintain the continuity of TreM resource and associated biodiversity. However, this approach may be difficult due to the widespread intensification of forest management and global climate change. Importancia de conservar los árboles viejos y grandes para la continuidad de los microhábitats relacionados Resumen La protección de las características estructurales, como los microhábitats relacionados a los árboles (MhAr), es una herramienta económica importante para la conservación de la biodiversidad que puede aplicarse en los paisajes boscosos extensos. Aunque el diámetro, especie y vitalidad del árbol influyen sobre el desarrollo de los MhAr, todavía se sabe poco sobre las relaciones entre la edad del árbol y el perfil. Modelamos los efectos de la edad y diámetro del árbol y las características del sitio sobre la riqueza y presencia de los MhAr en algunos de los bosques primarios más preservados de Europa, incluyendo los bosques mixtos de hayas y abetos, con una estrategia basada en los anillos de crecimiento y un conjunto con datos de 8038 árboles. Observamos un incremento generalizado en la riqueza de MhAr en los árboles viejos y grandes en ambos tipos de bosques. La presencia de grupos específicos de MhAr tuvo una relación variada con el diámetro y la edad del árbol, aunque algunos grupos de MhAr (p. ej.: epífitas) tuvieron una relación positiva más fuerte con la elevación y la especie del árbol. Mientras que muchos grupos de MhAr estuvieron asociados positivamente con la edad y diámetro del árbol, sólo dos grupos de MhAr en los abetos reaccionaron exclusivamente a la edad del árbol (galerías de insectos y savia expuesta) sin responder al diámetro. Por lo tanto, la retención de los árboles con fines de conservación basada en los diámetros parece ser una estrategia plausible con un riesgo bajo de subrepresentación de los MhAr. Ya que a mayor edad y diámetro del árbol hubo efectos positivos en el desarrollo de los MhAr, poner un mayor énfasis sobre la conservación de los árboles grandes y permitirles alcanzar una edad mayor, por ejemplo, a través del establecimiento de reservas de conservación, mantendría de mejor manera la continuidad del MhAr y de la biodiversidad asociada. Sin embargo, esta estrategia puede ser complicada debido a la intensificación generalizada de la gestión forestal y el cambio climático mundial. 【摘要】 保护结构特征, 如与树有关的微生境 (TreM), 是适用于大型森林景观生物多样性保护且具有成本效益的重要工具。虽然 TreM 的发展受到树木直径、物种和生存力的影响, 但人们对树龄和 TreM 基本特征之间的关系仍知之甚少。本研究利用基于树木年轮的方法和包含8038棵树的大型数据集, 模拟了树龄、直径和位点特征对欧洲一些最完整的温带原始森林 (包括山毛榉和云杉混交林) TreM 丰富度和出现率的影响。我们发现在这两种森林类型中, 古树和大树的 TreM 丰富度总体上有所增加。特定 TreM 类型的出现率与树龄和直径有不一致的关系, 但一些 TreM 类型 (如附生植物) 与树种和海拔有较强的正相关关系。虽然许多 TreM 类型与树龄和直径呈正相关关系, 但云杉林中只有2种 TreM 类型只与树龄有相关性 (昆虫孔道和裸露的白木质), 而与直径没有相关性。因此, 为了保护目的而根据树木直径保留树木似乎是一种普遍可行的方法, 这种方法对 TreMs 代表性不足的风险相当低。 由于更大的树龄和直径对 TreMs 的发展有积极作用, 因此更应强调对大树的保护, 使其生长到更大树龄, 来更好地保持 TreM 资源和相关生物多样性的连续性 (如通过建立保护区) 。然而, 由于森林管理和全球气候变化问题的普遍加剧, 这种方法可能也面临困难。【翻译: 胡怡思; 审校: 聂永刚】